2018
DOI: 10.1097/md.0000000000011968
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral percutaneous balloon kyphoplasty for osteoporotic vertebral compression fractures

Abstract: Background:Unilateral and bilateral percutaneous balloon kyphoplasty (PKP) are 2 main approaches for the treatment of patients with osteoporotic vertebral compression fractures (OVCFs). Numerous published systematic reviews and meta-analyses evaluating the effectiveness of 2 approaches remain inconclusive. In order to propose a significant principle to make decisions for comparing clinical safety and efficacy of unilateral versus bilateral PKP for treating OVCFs patients based on the currently best available e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
2
19
1
Order By: Relevance
“…PKP can reconstruct the vertebral body height, increase the stiffness of vertebral bodies, immediately stabilize the vertebral body, quickly relieve back pain, reduce the complications in bed, improve cardiopulmonary function, improve the quality of life of elderly patients and is currently the preferred treatment of OVCF [ 10 , 11 ].In recent years many scholars have proposed the use of a unilateral pedicle puncture in PKP [ 5 , 6 , 12 , 13 ]. Compared with bilateral PKP, unilateral PKP produced advantages such as a shorter surgery time, smaller dosage of cement, lower risk of cement leakage, and relieved a higher degree of intractable pain at short-term follow-up after surgery [ 14 ]. Indeed, unilateral puncture PKP can reduce both the operation time and complications of bilateral punctures [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…PKP can reconstruct the vertebral body height, increase the stiffness of vertebral bodies, immediately stabilize the vertebral body, quickly relieve back pain, reduce the complications in bed, improve cardiopulmonary function, improve the quality of life of elderly patients and is currently the preferred treatment of OVCF [ 10 , 11 ].In recent years many scholars have proposed the use of a unilateral pedicle puncture in PKP [ 5 , 6 , 12 , 13 ]. Compared with bilateral PKP, unilateral PKP produced advantages such as a shorter surgery time, smaller dosage of cement, lower risk of cement leakage, and relieved a higher degree of intractable pain at short-term follow-up after surgery [ 14 ]. Indeed, unilateral puncture PKP can reduce both the operation time and complications of bilateral punctures [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent comparative studies [14,15] found that unilateral PKP are safe and effective for OVCF patients as bilateral PKP, but need less radiation dose, less operation time and fewer cement volume. And several meta-analyses [16][17][18] proposed the similar viewpoints and suggested that unilateral PKP appeared to be superior to bilateral PKP in the treatment of OVCFs. Hence, unilateral PKP might be recommended to treat OVCF due to these advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported that the greater cement leakage in the unipedicular group to the spinal canal was caused by efforts to position the bone tamp more centrally during surgery. However, unipedicular KP is generally known to reduce the risks associated with placing large-bore needles in the spine [ 26 ] ; these risks include pedicle fracture, spinal canal invasion, nerve damage, cement leakage through the cannula tract, and spinal epidural hematoma. In this study, we found no significant differences in the degree of KA recovery between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that there is no consensus on whether bipedicular KP has similar efficacy to unipedicular KP, [ 20 , 22 , 23 ] or whether unipedicular KP is superior, as it has a shorter procedure time and requires less cement. [ 21 , 24 26 ] Therefore, this study aimed to compare the efficacies of bipedicular and unipedicular KP and determine which of the 2 methods is superior.…”
Section: Introductionmentioning
confidence: 99%